Licorice: From Pseudohyperaldosteronism to Therapeutic Uses - Sabbadin, Chiara; Bordin, Luciana; Donà, Gabriella; Manso, Jacopo; Avruscio, Giampiero; Armanini, Decio (Frontiers in Endocrinology, 2019)
Licorice has been used as a medicinal plant from 2.500 years. It shows a wide range of biological and pharmacological activities, including anti-inflammatory and immune regulatory actions. One of its most known effects is the induction of hypertension, and it can induce what appears to be pseudohyperaldosteronism, due to glycyrrhetinic acid, the main active component of the root. Glycyrrhetinic acid and metabolites block the 11 beta-hydroxysteroid dehydrogenase type 2 and also bind directly mineralocorticoid receptors as agonists. However, other interesting therapeutic uses of licorice are linked to its anti-androgen and estrogen-like activity, especially in the treatment of polycystic ovary syndrome in conjunction with spironolactone therapy. In this brief review, we report the main features and possible therapeutic uses of this ancient plant.